A Randomized Controlled Trial of an Automated Telephone Intervention to Improve Blood Pressure Control. Issue 9 (12th July 2013) - Harrison, Teresa N.; Ho, Timothy S.; Handler, Joel; Kanter, Michael H.; Goldberg, Ruthie A.; Reynolds, Kristi
Abstract : The objective of this study was to evaluate the effectiveness of a telephonic outreach program to improve blood pressure (BP) control among patients with hypertension. The authors identified adults 18 years and older with uncontrolled BP within the previous 12 months. Patients received either an automated telephone call advising them to have a walk‐in BP check (n=31, 619) or usual care (n=33, 154). The primary outcome was BP control at 4 weeks. Significantly more patients who received the intervention achieved BP control compared with the usual care group (32.5% vs 23.7%; P <.0001). Patients in the intervention arm with cardiovascular disease, chronic kidney disease, or diabetes mellitus achieved better BP control. Older age, female sex, and having a household income above the median were associated with BP control. When designing quality‐improvement interventions to increase BP control rates, health care organizations should consider utilizing an automated telephone outreach campaign.